Lansoprazole alleviates pressure overload-induced cardiac hypertrophy and heart failure in mice by blocking the activation of β-catenin. Issue 1 (24th January 2019) - Lin, Hairuo; Li, Yang; Zhu, Hailin; Wang, Qiancheng; Chen, Zhenhuan; Chen, Lin; Zhu, Yingqi; Zheng, Cankun; Wang, Yuegang; Liao, Wangjun; Bin, Jianping; Kitakaze, Masafumi; et al.
Abstract: Aims: Proton pump inhibitors (PPIs) are widely used in patients receiving percutaneous coronary intervention to prevent gastric bleeding, but whether PPIs are beneficial for the heart is controversial. Here, we investigated the effects of lansoprazole on cardiac hypertrophy and heart failure, as well as the underlying mechanisms. Methods and results: Adult male C57 mice were subjected to transverse aortic constriction (TAC) or sham surgery and then were treated with lansoprazole or vehicle for 5 weeks. In addition, cultured neonatal rat ventricular cardiomyocytes and fibroblasts were exposed to angiotensin II in the presence or absence of lansoprazole. At 5 weeks after TAC, the heart weight/body weight ratio was lower in lansoprazole-treated mice than in untreated mice, as was the lung weight/body weight ratio, while left ventricular (LV) fractional shortening and the maximum and minimum rates of change of the LV pressure were higher in lansoprazole-treated mice, along with less cardiac fibrosis. In cultured cardiomyocytes, lansoprazole inhibited angiotensin II-induced protein synthesis and hypertrophy, as well as inhibiting proliferation of fibroblasts. Lansoprazole decreased myocardial levels of phosphorylated Akt, phosphorylated glycogen synthase kinase 3β, and active β-catenin in TAC mice and in angiotensin II-stimulated cardiomyocytes. After overexpression of active β-catenin or knockdown of H + /K + -ATPase α-subunit, lansoprazole still significantly attenuated myocyte hypertrophy. Conclusion: Lansoprazole inhibits cardiac remodelling by suppressing activation of the Akt/GSK3β/β-catenin pathway independent of H + /K + -ATPase inhibition, and these findings may provide a novel insight into the pharmacological effects of PPIs with regard to alleviation of cardiac remodelling.